- Tindak Pidana Kekerasan Dalam Lingkungan Rumah Tangga yang Tidak Menyebabkan Penyakit: - - Anselmus Jefri Aldonny Pasaribu; Ermania Widjajanti (Reformasi Hukum Trisakti, 2023)
The Batu Sangkar District Court's ruling. In violation of Article 44 Paragraph (4) of Law Number 23 of 2004, the defendant, Dandi Arisman, who is the victim's husband, assaulted the victim by kicking the body of the motorbike she was riding. Despite the victim's minor injuries, she continued to perform his job at the time. The question put up is whether it is appropriate to apply Law No. 23 of 2004's Article 44 paragraph (1) to those who commit crimes. (Decision No. 113/Pid.Sus/2021/PN BSK) and what is the judge's sanction for those who use physical force in domestic situations? The research technique makes use of normative descriptive analytical research with secondary data. The findings of the government's investigation and discussion led to the publication of Law No. 23 of 2004 as a regulation. When the defendant's conduct were compliant with Article 44, paragraph 4, of Law No. 23 of 2004, and they resulted in serious injury to the victim as well as the victim's inability to perform her job as a result of those injuries, this rule has permanent legal force. The judge's judgment is not in line with the UUPKRT, which leads to misunderstandings, according to the conclusion.